The Impact of Human Resource Practices on The Employee Performance in The Private General Hospitals of Karachi (KASBIT Business Journal, 2023)
The focus of the current study was on Karachi's general hospitals, which sought to determine the impact of human resource practices on employee performance. The respondents to this survey were healthcare workers, doctors, and other healthcare professionals. During this research study, the following dimensions of human resource practices were measured: training and development, employee performance, employee empowerment, and employee compensation. A 5-point Likert scale was used to measure the responses. The sample size was 120, which was entirely based on the healthcare workers in the hospitals of Karachi. The questionnaires were personally administrated, and simultaneously the data was also collected by the online data collection method. Further, IBM SPSS was used to analyze the data. The findings indicate that hospitals that implement and use human resource practices within their facilities were more likely to have more employees with higher performance than hospitals that did not implement such practices. This contrasts with employees who worked for organizations that did not implement such practices.
Keywords: HR Practices, Training and development, employee performance, employee empowerment, and employee compensation.